EFIKASI TERAPI PERILAKU KOGNITIF BERBASIS DARING TERHADAP GEJALA DEPRESI DAN ANSIETAS PADA PASIEN PARKINSON: SEBUAH KAJIAN LITERATUR - Dyson, Nathaniel Gilbert (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2023)
Background: Parkinson’s Disease (PD) is a chronic neurodegenerative disease with neuropsychiatric symptoms such as depression and anxiety, which are often overlooked or untreated. Psychiatric treatment which is tailored especially for PD patients is still limited. Objectives: To determine the efficacy of internet-based cognitive behavioral therapy (ICBT) in treating depression and anxiety in PD patients. Methods: Literature searching is done in online databases PubMed, Cochrane, SCOPUS, ScienceDirect, and EBSCOHost. Results: Significant improvement of depression and anxiety score in patients treated with ICBT. ICBT also has a higher adherence and completion rate because of its flexibility and convenience. Factors affecting ICBT include duration of disease, patients’ perception, and patient-clinician relationship. Conclusion: ICBT is an effective alternative therapy to treat neuropsychiatric symptoms in PD patients, especially depression and anxiety. Overall, studies show improvement of depression and anxiety measured with standardized questionnaires, and patients show good adherence and high completion rate with this therapy. Keywords: Internet-based cognitive behavioral therapy, neuropsychiatric symptoms, Parkinson’s Disease